The Role of the Adipokine Resistin in the Pathogenesis and Progression of Epithelial Ovarian Cancer - Parafiniuk, Klaudia; Skiba, Wiktoria; Pawłowska, Anna; Suszczyk, Dorota; Maciejczyk, Aleksandra; Wertel, Iwona (Biomedicines, 2022)
Obesity is a civilization disease associated with an increased risk of developing cardiovascular diseases, diabetes, and some malignancies. The results concerning the relationship between obesity and epithelial ovarian cancer (EOC) are inconclusive. The higher incidence of neoplasms in obese subjects has led to the development of the adipokine hypothesis. Omental adipocyte cells interact with cancer cells, promoting their migration and metastasis via the secretion of adipokines, growth factors, and hormones. One of the adipokines is resistin. It was shown in vitro that resistin stimulates the growth and differentiation of ovarian cancer cells. Moreover, it increases the level of angiogenesis factors, e.g., matrix metalloproteinase 2 (MMP-2) and vascular epithelial growth factor (VEGF). Additionally, resistin induces epithelial–mesenchymal transition (EMT) and stemness in EOC cell lines. A positive correlation has been shown between a higher level of resistin expression and the stage of histological differentiation of EOC or the occurrence of lymph node metastases. In addition, the overexpression of resistin has been found to act as an independent factor determining disease-free survival as well as overall survival in EOC patients. Growing evidence supports the finding that resistin plays an important role in some mechanisms leading to the progression of EOC, though this issue still requires further research.